2011
DOI: 10.1182/blood-2010-10-313791
|View full text |Cite
|
Sign up to set email alerts
|

Novel associations between activating killer-cell immunoglobulin-like receptor genes and childhood leukemia

Abstract: Acute lymphoblastic leukemia of pre-B cells (pre-B ALL) is the most frequent form of leukemia affecting children in Western countries. Evidence is accumulating that genetic factors play an important role in conferring susceptibility/ resistance to leukemia in children. In this regard, activating killer-cell immunoglobulin-like receptor (KIR) genes are of particular interest. Humans may inherit different numbers of the 6 distinct activating KIR genes. Little is known about the impact of this genetic variation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
3
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 37 publications
0
44
3
2
Order By: Relevance
“…Although two recent studies reported higher frequency of activating KIR genes, such as KIR2DS1, KIR2DS3 and KIR2DS4 in patients with CML and ALL [22,23], we couldn't reproduce these findings in our cohort. Our findings are thus in agreement with those reported from Babor et al, who also found very similar frequencies of KIR genes among haematological patients and healthy controls with European origin [24].…”
Section: Discussioncontrasting
confidence: 63%
“…Although two recent studies reported higher frequency of activating KIR genes, such as KIR2DS1, KIR2DS3 and KIR2DS4 in patients with CML and ALL [22,23], we couldn't reproduce these findings in our cohort. Our findings are thus in agreement with those reported from Babor et al, who also found very similar frequencies of KIR genes among haematological patients and healthy controls with European origin [24].…”
Section: Discussioncontrasting
confidence: 63%
“…1 Obviously, these results contradict those reported recently by us. 2 Interestingly, the frequencies of these genes in controls are more or less comparable in both studies. Babor and colleagues mentioned technical challenges associated with PCRbased KIR genotyping due to strong similarities between KIR genes and their many alleles.…”
Section: Responsementioning
confidence: 70%
“…These observations are in line with a more recent case-control study including 109 children suffering from ALL. Almalte et al found that inheriting a higher number of activating KIR genes was associated with significant reduction in risk for development of ALL (66). These findings support the important influence of activating KIRs in pediatric ALL not only in the setting of haploidentical transplantation but also for the development and maybe the course and therapy of pediatric ALL.…”
Section: Exploiting Haploidentical Sctmentioning
confidence: 76%